Opportunities and challenges for sugar replacement in chocolate: a review - Thomas, Rebecca (My University, 2026)
This review explores the current landscape of sugar reduction in chocolate, focusing on the challenges and opportunities presented by various sweetener alternatives. Sucrose, which comprises nearly half of a chocolate’s composition, plays a multifaceted role as a sweetener, bulking agent, and modulator of mouthfeel and rheology. Traditional sugar substitutes such as polyols (maltitol, xylitol, isomalt, sorbitol) and fibers (inulin, polydextrose, maltodextrin) are widely used, often in combination with high-intensity sweeteners to mimic the physical and sensory properties of sucrose. While polyols and fibers can partially replicate the functionality of sucrose, their use is generally limited by digestive discomfort and the need for complex ingredient blends. Recent research has explored novel alternatives including rare sugars such as tagatose and allulose, palm and coconut sugars, mulberry molasses microcapsules, red beetroot powder, and date powder, each offering unique benefits and challenges in terms of rheology, microstructure, and consumer acceptability. Studies consistently show that no single substitute can fully match all the sensory and physical attributes of traditional sucrose-sweetened chocolate. Optimal results are achieved through meticulously crafted blends of bulk sweeteners and high-intensity sweeteners, with ingredient selection influenced by chocolate type (white, milk, or dark) and desired consumer target. Sensory evaluations highlight the importance of balancing sweetness, texture, and flavor, while instrumental analyses reveal significant impacts on viscosity, hardness, and fat and sugar crystallization. This review concludes that further research is needed to identify novel ingredient combinations that more closely replicate the properties of sucrose, minimize gastrointestinal impact, and meet consumer expectations for taste and health-consciousness in reduced-sugar chocolate products.
Keywords: Chocolate; Sugar reduction; Microstructure; Rheology; Sensory